The influence of social media marketing on purchase intention with brand awareness and halal awareness of Scarlett products : SMM, Brand Awareness, Halal Awareness, Purchase Intention, mediation analysis - Niken Aprilia Mulyadi; Hendri Andi Mesta (Marketing Management Studies, 2023)
The purpose of this study is to examine the effect of social media marketing on purchase intention in Padang, using brand awareness and halal awareness as mediators of scarlett products. The population of this research is the people of Padang city who have used social media. The survey attracted 140 participants. Data acquired through the distribution of surveys is processed using SmartPLS software. The results of this study indicate that (1) social media marketing has a large and favorable impact on purchase intention, (2) social media marketing has a large and favorable impact on brand awareness, (3) social media marketing has a large and favorable impactct on halal awareness, (4) brand awareness has a positive and significant effect on purchase intention, (5) halal awareness has no significant effect on purchase intention (6) social media marketing has a positive and significant effect on purchase intention with brand awareness as mediation, (7) social media marketing has no significant effect on purchase intention with halal awareness as mediation.